Hubungan Dukungan Keluarga dengan Tingkat Stres Mahasiswa Rantau yang Mengerjakan Skripsi - Niken Ayu Atiawardani; Tri Anjaswarni; Sulastyawati Sulastyawati; Kissa Bahari (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2025)
This study aims to analyze the relationship between family support and the stress levels of out-of-town students working on their thesis in the Bachelor of Applied Nursing Study Program at Poltekkes Malang. This research uses an observational method with a correlational design. The population consists of all out-of-town students working on their thesis in the Bachelor of Applied Nursing Study Program at Poltekkes Malang, totaling 131 students, from which 89 respondents were selected through purposive sampling. The analysis test uses the Spearman correlation. The analysis results show a significant relationship between family support and the stress levels of out-of-town students working on their thesis, with a p-value of 0.024 and an r value of -0.240. This indicates that the strength of the relationship is low, and the direction is negative, meaning that the higher the family support, the lower the stress levels experienced. Students are encouraged to reduce stress caused by their thesis by utilizing family support and seeking support from other sources, such as peers or significant others